Sensory material architectures: Concepts and methodologies for spatial tectonics and tactile responsivity in knitted textile hybrid structures. (March 2016) - Ahlquist, Sean
As the knowledge of material computation advances, continuing the seamless integration of design and fabrication, questions beyond materialization can be addressed with a focus on sensing, feedback, and engagement as critical factors of design exploration. This article will discuss a series of prototypes, design methodologies, and technologies that articulate a textile's micro-architecture, at the scale of fibers and stitches, to instrumentalize simultaneous structural, spatial, and sensory-responsive qualities. The progression of research displays an ever-deepening instrumentalization of fiber structure and its implications to form definition and responsivity, in creating form- and bending-active structures. The research results in a more refined definition of material behavior as the innate phenomena which emerge at the moment of textile fabrication. Ultimately, the architecture, in its materiality and physical, visual, and auditory responsivity, is designed to address specific challenges for children in filtering multiple sensory inputs, an underlying factor of autism spectrum disorder.